Maternal contribution to the reproductive potential of a recovering fish stock: variability in the fecundity and condition of haddock ( Melanogrammus aeglefinus ) on the Scotian Shelf - Blanchard, JL (Department of Biology Dalhousie University Halifax, 2000)
The maternal contribution to the reproductive potential of a fish stock can beassessed by measuring the fecundity and condition of adult females. In turn, this canprovide a more accurate measure of potential egg production than traditional estimates ofSpawning Stock Biomass (SSB). This study represents the first comprehensive evaluationof the reproductive potential of the Eastern Scotian Shelf (ESS) haddock( Melanogrammus aeglefinus ) stock. Three years of fecundity data were collected over the period 1997-1999 for theEastern Scotian Shelf haddock and data were also collected for the neighbouring,Southwest Scotian Shelf haddock stock in 1998 and 1999. Fecundity-body sizerelationships were determined for the three years of data collected and were highlyvariable compared to the neighbouring southwestern Scotian Shelf stock. Significantinter-annual differences in the intercepts of these relationships were observed over the1997-1999 period and appeared to be reflective of inter-annual differences in condition.Relative to other haddock stocks throughout the North Atlantic, ESS haddock exhibitedthe lowest and most variable fecundity-length relationship. Multiple regression models incorporating length and condition were developedusing three different measures of condition: liver index (H.S.I.); Fultons condition index(K) and length specific weight (with a length*weight interaction term). All measures ofcondition contributed to explaining additional variation in fecundity-at-length (from 15-19%). H.S.I. explained the most variation, followed by length specific weight, thenFultons K. The stock reproductive potential was reconstructed for a two decade period(1979-1999) by incorporating the fecundity equations into a length based populationmodel. This yielded annual estimates of Total Egg Production (TEP). Results showed thatTEP has declined over that period with evidence of a recent increase in 1999. The declinewas more drastic when TEP was separated for repeat spawners (fish above 40.5 cm).Also, there appeared to be a stronger relationship between TEP by repeat spawners andrecruitment than the relationship between VPA-based SSB.The TEP estimates based onrepeat spawners are more representative of the quantitative and qualitative factorscontributing to reproductive potential and hence this approach is a more accurate methodof estimating recruitment.